2019
DOI: 10.1002/chem.201903814
|View full text |Cite
|
Sign up to set email alerts
|

Intersystem Crossing in Naphthalenediimide–Oxoverdazyl Dyads: Synthesis and Study of the Photophysical Properties

Abstract: Oxoverdazyl( Vz) radicalu nits were covalently linked to the naphthalenediimide (NDI) chromophore to study the effect of the radicalo nt he photophysical properties, especially the radicale nhanced intersystem crossing (REISC), which is ap romisinga pproach to develop heavyatom-free triplet photosensitizers. Rigid phenylo re thynylphenyll inkers betweent he two moieties were used, thus REISC andf ormation of doublet (D 1 ,t otal spin quantum number S = 1/2) and quartet states (Q 1 , S = 3/2) are anticipated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…However, both D 1 and Q states are with the PBI moiety in the triplet state, therefore, the D 1 and the Q states are indistinguishable in optical transient absorption spectra [47] . We didn't observe biexponential decay of the triplet state, which is different from the recently reported NDI‐verdazyl radical dyads [82] …”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…However, both D 1 and Q states are with the PBI moiety in the triplet state, therefore, the D 1 and the Q states are indistinguishable in optical transient absorption spectra [47] . We didn't observe biexponential decay of the triplet state, which is different from the recently reported NDI‐verdazyl radical dyads [82] …”
Section: Resultscontrasting
confidence: 98%
“…Interestingly, PBI−NH shows a triplet state lifetime of 15.0 μ s (intermolecular photosensitizing method, see Figures S21 in Supporting Information). These results infer that there is an electron spin‐spin exchange interaction between the radical and the PBI moiety in PBI−TEMPO , by which the triplet state of the PBI may be shortened [56,82] …”
Section: Resultsmentioning
confidence: 87%
“…The data were analyzed with single value decomposition (SVD) and global fitting, employing a linear unidirectional decay scheme, obtaining the time constants and the Evolution Associated Difference Spectra (EADS). In previously reported radical‐containing molecules, for instance, NDI labeled with TEMPO, the ISC occurs within 338 ps, [7] whereas for the NDI‐veradazyl dyad a charge recombination‐induced ISC was observed (time constant: 1.40 ps), instead of the expected electron spin‐spin exchange interaction‐induced ISC [41] . Furthermore, in the compact perylene‐NO⋅ dyad, the REISC takes place within 1 ps [26] .…”
Section: Resultsmentioning
confidence: 84%
“…The fluorescence spectra of the dyads were also measured in solvents of different polarities, the results indicated that the emission is quenched in all solvents compared with the pristine perylene (Figure S24 and S25 in the Supporting Information). The strong quenching of the perylene fluorescence in the dyads can be ascribed to different reasons, including Förster Resonance Energy Transfer (FRET) towards the verdazyl moiety, photoinduced electron transfer (PET), spin‐spin exchange interactions to form high spin states or radical enhanced ISC [7,41,44–46] …”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, mode-locked Ti:sapphire lasers can routinely provide highly stable pulses, even as short as about 4 fs. The resulting fundamental 800 nm laser mode can be efficiently tuned in the UV and visible spectral region in order to provide suitable pump wavelengths [7,[21][22][23]. The wide tunability is accomplished by means of OPA (Optical Parametric Amplification), OPG (Optical Parametric Generation) or by Second Harmonic (SHG) and Third Harmonic (THG) Generation.…”
Section: Basic Principles Of Transient Absorption Spectroscopy (Tas) mentioning
confidence: 99%